Effect of fatigue loading on bonding shear strength at the interface between two layers concrete - Ali, Maisarah; Tsuchiya, Itsuo; Matsui, Shigayuki (American Society of Civil Engineering, 1999)
In Japan,one of the methods to repair and strength concrete bridge decks is the Thickness Increasing Method where a thin new concrete layer is cast on top or bottom of the existing concrete slab. After the repair work has been completed the bridge is open to traffic and the bonded interface is subjected to normal and shear stresses from the traffic. Torque stress were carried out on beam specimens to evaluate the bonding shear strength at the interface between new and old concrete after they were subjected to fatigue loading. From the experiments, a clear relationship between stress level at various specimens' positions and the bonding shear strength after the application of fatigue loading could not obtained. However, a trend of bonding shear strength after the application of fatigue loading could be obtained. The higher magnitude of the load and cycles of fatigue loading the more the reduction in bonding shear strength occurs.